Potentially Inappropriate Medications (PIMs) in Elderly Hypertensive Inpatients using 2023 AGS Beers Criteria: A Cross-Sectional Study : Prevalence and predictors of PIM exposure among elderly inpatients - Humaira Issa; Retnosari Andrajati; Nadia Farhanah Syafhan; Muhammad Adil Khan (JSFK (Jurnal Sains Farmasi & Klinis), 2026)
Polypharmacy and complex pharmacotherapy are common in older adults with hypertension and increase the risk of potentially inappropriate medications (PIMs). This study aimed to determine the prevalence, pattern, and predictors of PIM exposure among elderly hypertensive inpatients at Universitas Indonesia Hospital (RSUI) using the American Geriatrics Society 2023 updated AGS Beers Criteria®. A retrospective cross-sectional study was conducted using de-identified electronic medical records. From 1,265 admissions screened in 2023-2024, 200 hypertensive inpatients aged 65 years or older were included. Inpatient prescriptions were evaluated using the 2023 AGS Beers Criteria and classified by Beers categories. Logistic regression was used to identify predictors of PIM exposure. The mean age was 72.1 ± 6.5 years, and 55.0% were female; polypharmacy (≥5 medications) occurred in 85.5%. Overall, 83.0% received at least one Beers-listed medicine, most commonly Category 3 (“use with caution”) PIMs (72.5%), followed by Category 1 (“avoid”) (26.0%) and Category 4 (23.0%). Diuretics (furosemide, hydrochlorothiazide) and clonidine were frequent PIM-related medications. Polypharmacy was the only significant independent predictor of PIM exposure. These findings support systematic medication review and deprescribing-focused interventions during hospitalization.